Safety Profile of Warfarin versus Dabigatran in Adult Patients with Non-valvular Atrial Fibrillation – A Prospective Cohort Study - Rabbani, Anam A; Rao, Padma GM; Wadhwa, Tarun; Gupta, PK (Indian Journal of Pharmacy Practice)
Context: Atrial fibrillation is the most commonly encountered sustained cardiac arrhythmia associated with extensive cardiovascular morbidity and mortality. Warfarin is the most recommended drug therapy for the prevention of thromboembolic events or stroke in patients with atrial fibrillation. Due to availability of newer drugs like dabigatran, the need for frequent PT/INR monitoring and bleeding risk has reduced drastically. Although, studies are lacking regarding its safety profile and therapeutic use in clinical practice. Aim: The main objective of the present study was to assess the safety profile of warfarin versus dabigatran in patients with non-valvular atrial fibrillation. Materials and Methods: This was a prospective cohort study carried out for a period of nine months. All adult patients, who were prescribed with either warfarin or dabigatran in non-valvular atrial fibrillation were included in the study. Patients were monitored initially for occurrence of adverse drug events and subsequently during their follow-up visits at 3 and 6 months. Reported ADEs were analyzed for various clinical characteristics and causality, severity and preventability using standard assessment scales. Results: A total of 75 patients (35 in warfarin and 40 in dabigatran cohort) were recruited. Out of 75, 38 patients experienced 70 ADEs (31 in warfarin and 39 in dabigatran cohort) which accounted for an overall incidence of 51%. Elevated coagulation profile (20%) followed by chest discomfort (10%), thrombocytopenia (7.14%), abdominal pain (7.14%), anemia (10%), gastritis (5.71%) and hematemesis (5.71%) were the most common reported ADEs among others. Dabigatran (55.71%) was associated with higher number but less severe ADEs as compared to warfarin (44.28%). Majority of ADEs were found to be probable (53%) in nature, moderate (57%) in severity, predictable (71%) and not preventable (40%). Conclusion: Dabigatran being a costly alternative appears to be safer than warfarin. Key Messages: Dabigatran appears to be safer than warfarin. Less frequent PT/INR monitoring, reduction in bleeding events and safer administration being the most probable reasons for preferring dabigatran in patients with non-valvular atrial fibrillation.
Keywords: Adverse drug events; Anticoagulants; Dabigatran; Non-valvular atrial fibrillation; Safety profile; Warfarin.